Ob 85-letnici Pavla Apovnika: Cui honorem, honorem – Čast, komur čast - Karničar, Ludvik (Slavia Centralis, 2020)
The author of the article congratulates to Pavel Apovnik, a Slovenian lawyer, publicist and lexicographer, on his 85th birthday and presents him in a short biography.
Keywords: Pavel Apovnik; 85th birthday; resume; congratulations; celebrations